Estimation of Lead, Copper and Zinc Elements in Livers and Kidneys of Columba livia domestica which infected with Raillietina sp. in Al-Nassiriyah City/ South of Iraq. - Manar G. Al-Hussaini ,; Afrah A. Maktoof, (University of Thi-Qar Journal of Science, 2021)
The present study aimed to evaluate the effect of the concentrations of Lead (Pb), Copper (Cu) and Zinc (Zn), in liver and kidney of Columba livia domestica infected with Raillietina sp. 300 birds of C. livia were collected from local market at Al-Nassiriyah city. The birds were divided in to two groups: first one was infected with Raillietina sp. and second group was healthy group. 129 birds were infected with tapeworms which belong to three genera: Raillietina sp., Cotugina sp., Apronia sp., with infection rates of 52,8%, 27,9% and 19,1% respectively, for the period from April 2019 to February 2020. Heavy element concentrations were measured by flame atomic absorption spectrophotometer (FAAS). The highest Pb concentration in liver was elevated in Summer (0.589 µg/ g) dry weigh. While , the highest kidney Pb concentration was equal in Summer and Spring (0.440 µg/ g) dry weigh. In liver, the highest concentration of Cu was in Summer (0.799 µg/ g) dry weight, however, in kidney, the concentration of Cu was in Spring (0.610 µg/ g) dry weight. In Winter, Zn concentration was elevated in livers and kidneys (1.00 and 1.21 µg/ g, dry weigh respectively) In Raillitiena sp. the highest concentration of Pb was in Summer (0.608 µg/ g) dry weigh, however the highest concentrations of Cu and Zn were in Winter (1.42 and 1.99 µg/ g dry weigh for Cu and Zn, respectively).